2016
DOI: 10.1007/s11356-016-6809-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of linear alkylbenzene sulfonate (LAS) on the interspecific competition between Microcystis and Scenedesmus

Abstract: The widespread use of detergents increases the concentration of surfactant in lakes and reservoirs. High surfactant loads produces toxicity to algae; however, the influence of the increasing surfactant on the competition between algae is not clear. In this paper, different amounts of linear alkylbenzene sulfonate (LAS) were added to test the effects of LAS on the competition between Microcystis aeruginosa and Scenedesmus obliquus under eutrophic condition. In single culture, the growth of S. obliquus was promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…This was due to that Cu 2+ are essential micronutrient for Microcystis 51. Additionally, it has also been well documented that low-level contaminants promote Microcystis growth525354. However, the sensitivity or tolerance to heavy metals varies amongst different algae and this variation caused that the beneficial concentration of Cu 2+ for M. flos-aquae and M. viridis inhibited growth of M. aeruginosa and M. wesenbergii .…”
Section: Discussionmentioning
confidence: 99%
“…This was due to that Cu 2+ are essential micronutrient for Microcystis 51. Additionally, it has also been well documented that low-level contaminants promote Microcystis growth525354. However, the sensitivity or tolerance to heavy metals varies amongst different algae and this variation caused that the beneficial concentration of Cu 2+ for M. flos-aquae and M. viridis inhibited growth of M. aeruginosa and M. wesenbergii .…”
Section: Discussionmentioning
confidence: 99%
“…The Lotka-Volterra competitive model [28] was used to calculate the population dynamics of the two species under the stress of organic compounds in co-cultures [14,15], which was calculated using the following formula:NmnNmn1tntn1=rmnNmn1(KmnNmn1αNcn1)Kmn NcnNcn1tntn1=rcnNcn1(KcnNcn1βNmn1)Kcn where N mn ( N mn − 1 ) and N cn ( N cn − 1 ) represent the cell concentrations of M. aeruginosa and C. pyrenoidosa , respectively, when they were co-cultured at day t n ( t n − 1 ); r mn and r cn are the intrinsic growth rates of M. aeruginosa and C. pyrenoidosa , respectively, which are calculated according to the mono-cultures; K mn and K cn are the carrying capacity of each unit of cell concentrations of M. aeruginosa and C. pyrenoidosa respectively in mono-cultures; α and β are the competition coefficients in co-cultures; α indicates the inhibition of C. pyrenoidosa on M. aeruginosa ; and β represents the inhibition of M. aeruginosa on C. pyrenoidosa .…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, some studies have shown that organic pollutants (such as alkylbenzene sulfonate and pentachlorophenol) have the potential to overturn algal community structure [14,15]. For example, M. aeruginosa competed over Scenedesmus obliquus in co-cultures without alkylbenzene sulfonate (LAS), while the result was opposite when LAS (20 μg mL −1 ) was added in co-cultures [15]. Similarly, the effects of pentachlorophenol (PCP) on M. aeruginosa and Chlorella vulgaris were studied in co-cultures [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low concentration of pentachlorophenol (1 µg L − 1 ) that closed to the concentration in surface water stimulated the growth of M. aeruginosa, a shift dominance from M. aeruginosa to Chlorella vulgaris was observed when pentachlorophenol was over 0.25 mg L − 1 (de Morais et al 2014). M. aeruginosa outcompeted Scenedesmus obliquus in co-culture without linear alkylbenzene sulfonate (LAS) or 1 mg L − 1 of LAS, while S. obliquus dominated with above 20 mg L − 1 of LAS (Zhu et al 2016). Similarly, the effect of phenol on competition between M. aeruginosa and Chlorella pyrenoidosa in coculture were investigated (Tan et al 2019a), described that phenolic pollution overturned the competition between both species.…”
Section: Introductionmentioning
confidence: 99%